Influence of technological innovation characteristics on the survival period of SMEs in the service industry: Evidence from Korea - Jun-won Lee (Journal of Innovation & Knowledge (JIK), 2023)
This study analyzes the effects of innovation and innovation characteristics on the survival of Small and Medium-sized Enterprises (SMEs) in the service industry. After analyzing around 22,300 innovative SMEs in Korea's service industry using Kaplan-Meier analysis, it is confirmed that the better the overall technological prowess (T-grade), the longer the survival period until delinquency (overdue payments for more than three months) and default. The technological innovation characteristics that significantly affect the survival period are derived using a time-dependent Cox model. Owner capability, productization capability, and profit prospects are found to positively affect the survival period of excellent SMEs, while R&D capability, technology superiority, and market status are found to have a negative effect. From an optimization perspective, if R&D capability is above an appropriate level, it can hinder the survival period of SMEs. Thus, it is interpreted that the more positive the market status, the more negative the survival period, because it accelerates the inflow of new competitors. Considering that owner capability, productization capability, and profit prospects are appraisal items based on business feasibility along with the technological prowess of SMEs, it is concluded that technology with business feasibility has a significantly positive effect on the survival period of innovative SMEs in the service industry.
Keywords: O32; 650; Small and Medium-sized Enterprises; Technological innovation characteristics; Survival period; Business feasibility; Technological prowess